EVERYDAY PLACES: WHY NEIGHBOURHOODS MATTER FOR PEOPLE LIVING WITH DEMENTIA. (11th November 2018) - Clark, A; Ward, R; Campbell, S; Manji, K
Abstract: This paper provides an experientially-grounded exploration of the relationships and connections that figure in the lives of people living with dementia. Existing research has identified clear roles for neighbors and others living locally in supporting older people. Social interactions between individuals in public and 'pseudo-public' places are also well-documented for generating both civilizing and alienating experiences. The paper extends these ideas by drawing on longitudinal research deploying a creative mix of qualitative methods, including network mapping, mobile interviews and home tours with almost 100 people living with dementia and their supporters in the UK. It will consider experiences of developing and maintaining connections with non-intimate others encountered during the routine ebb and flow of everyday life for ongoing support as well as help in situations of crisis. Consequently, the paper advances understanding of how people living with dementia are supported by, and can contribute to, the neighborhoods where they live.